XAS study of Ru doped n=1, 2 Ruddlesden-Popper manganites - Sikora, M; Oates, C; Szczerba, W; Kapusta, C; Zukrowski, J; Zajac, D; Borowiec, A; Ruiz-Bustos, R; Battle, P; Rosseinsky, M (2007)
We report on the results of X-ray absorption near edge structure (XANES) studies at the Mn:L2,3, Ru:K and O:K edges of novel manganites, Sr2Mn0.5Ru0.5O4 and Sr3MnRuO7. Measurements were carried out on polycrystalline powder samples at room temperature. From the analysis of the XANES spectra the average manganese valences of 3.4 in bilayer Sr3MnRuO7 and 3.1 in single layer Sr2Mn0.5Ru0.5O4 are obtained. The corresponding average valences for Ru ions are 4.6 and 4.9, respectively. This indicates that Ru doping gives rise to a decrease of Mn valence, whereas Ru valence increases, compared to Mn(IV) and Ru(IV) in undoped compounds. The effect of charge disproportionation is stronger in the single layered compound than in the bilayered one. © 2007 Elsevier B.V. All rights reserved.